Motor Function in Irritable Bowel Syndrome - Michael Camilleri (Canadian Journal of Gastroenterology)
The evidence supporting a role of abnormal motor function in irritable bowel syndrome (IBS) is reviewed. Symptoms commonly present in IBS patients, such as vomiting, diarrhea, constipation or incomplete rectal evacuation, indicate that a motor disorder is implicit as either a primary or secondary disturbance. Physiological studies implicate a disturbance of transit through the small bowel and proximal colon, and abnormal motor responses of the rectum to distention in IBS patients. Intestinal contractions (physiological or ‘abnormal’) are associated with the sensation of pain, suggesting that these contractions are interactions between abnormal motor and sensory functions in IBS. Therapies aimed at correcting abnormal transit or antispasmodics are the main pharmacological approaches to the relief of IBS, and, although the latter are not always effective in the long term response to treatment, they support the role of dysmotility in IBS. Most novel therapies under trial probably modulate both sensory and motor functions, and are discussed briefly. In summary, the weight of clinical, physiological and pharmacological evidence supports a role of abnormal motility in IBS.